(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Science-based laws are more and more common, due to the scientific and technical progress. This phenomenon imposes to (re)think the role of the legislator as well as the judge. The law establishing mandatory vaccinations is one example of this complex debate: starting from the important decision n. 5/2018 of the Constitutional Court, this paper aims at analyzing the different and challenging issues connected to the regulation of mandatory vaccinations, concerning the balance between individual and collective dimension of the right to health, the competence of Regions but also the importance of science-based data in the legislative and judicial process.